Third party assisted conception across cultures : social, legal, and ethical perspectives - Blyth, Eric; Landau, Ruth, 1946- (Jessica Kingsley Publishers, 2004)
Involving a third person in a child's conception raises many difficult issues and dilemmas. This book provides a comprehensive guide to the place of third party assisted conception within health care provision, drawing on local ethical and religious standpoints as well as political and economic factors. Eric Blyth and Ruth Landau have brought together authors from a broad range of professional backgrounds to consider the social, legal and ethical aspects of third party assisted conception in in thirteen countries dispersed through North and South America, Africa, Europe, Asia and Australasia.